Predominance of M1UK type strains and their clinical associations in invasive Streptococcus pyogenes infections in Japan, 2023–2025 - Shigeo Hanada; Misako Takata; Miyuki Baba-Morozumi; Junichi Sasaki; Satoshi Iwata; Shigeki Nakamura; Kimiko Ubukata (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Abstract Purpose The clinical relevance of M1 UK type strains of Streptococcus pyogenes in Japan remains insufficiently defined. We investigated the molecular epidemiology of M1 UK type strains and evaluated their clinical associations among adults with invasive group A Streptococcus (iGAS) infections. Methods We conducted a nationwide multicenter surveillance study of iGAS infections from December 2023 to March 2025. Molecular typing, profiling of M1 UK -associated single-nucleotide polymorphisms (SNPs) in the rofA , gldA , and pstB regions, and emm -cluster assignment were performed. Adult clinical characteristics and outcomes were compared between M1 UK type and non-M1 type infections after exclusion of the single adult M1 global case. Results Among 155 patients in the molecular epidemiology cohort, M1 UK type strains accounted for 58 isolates, whereas only one M1 global isolate was identified. Historical analysis showed that M1 global predominated among isolates collected in the early 2010s, whereas M1 UK type strains were detected mainly in recent periods. In adult clinical comparisons, M1 UK type infection was associated with streptococcal toxic shock syndrome (STSS; p = 0.004) and necrotizing fasciitis ( p < 0.001). In multivariable analysis, younger age, necrotizing fasciitis, and serum creatinine ≥ 2.0 mg/dL were associated with M1 UK type infection. Conclusion M1 UK type strains were important contributors to contemporary iGAS infections in Japan and were associated with severe clinical presentations, supporting sustained molecular surveillance beyond conventional emm typing.